Testing & scrutinizing the methodology of design thinking through studying/analyzing gamification approach to induce/support behavioral change to reduce CB littering - Kumar, Rishabh; Ryška, Tomáš, 1976-; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
This Master’s thesis uses the design thinking process to create a viable, user-centric design of an effective method ‘Gamified awareness program’ which would serve as a way to minimize CB littering in the selected site – campus of Prague University of Economics and Business, Prague. Ethnographic research was conducted on various users (CB litterers) over a period of 2-3 months in an iterative manner until saturation in the results were experienced. Behaviour and motivation behind littering was the key concept to be understood via the ethnographic research which included participant observation, non-formal and semi-structured interviews and written fieldnotes which were the analysed. A combination of key findings of the primary research and insights gained from the scientific body of the state-of-the-art literature serves as a justification of each design element. Gamified awareness program aims towards inducing change in the behaviour with the help of its traits such as achievability, challenging, credibility, being feedback-oriented and lastly meaningful. Feasibility study is provided towards the end of the thesis to showcase the design as a realizable approach.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses